(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Thyroid gland diseases are among the most common diseases in the field of endocrinology. The pathology of the cardiovascular system not only affects the patient’s quality of life, but also significantly increases the risk of failure of the operation, which is the only radical method of treatment. Therefore, most authors of many scientific studies consider existing and developing thyrotoxicosis as an indication against selective surgery. In recent years, the possibilities of anesthesiological methods used in operations on the thyroid gland have expanded significantly. The article examines the preparation of patients with toxic and non-toxic goitre for surgery, as well as the treatment of these patients in the perioperative period.